Analisis Kelayakan Ekonomi Pembangunan Jalan Baru Titik 7 dan 8 Ruas Singaraja–Mengwitani - I Gede Wahyu Putra Winarta; Putu Alit Suthanaya; Dewa Made Priyantha (Institut Teknologi Garut, 2025)
The development gap between North and South Bali has driven the construction of a new road along the Singaraja–Mengwitani section as a provincial strategic project. This study aims to conduct an ex-post economic feasibility evaluation at Points 7 and 8 by analyzing savings in Vehicle Operating Costs (VOC) and value of time, assessing feasibility through both direct and indirect benefits (increase in Regional Own-Source Revenue/PAD), and testing the robustness of results through sensitivity analysis. The research method is quantitative, using secondary data and traffic performance analysis based on PKJI 2023. The quantification of VOC benefits refers to Ministry of Public Works Guidelines No: Pd T-15-2005-B, while investment feasibility is measured using NPV, BCR, and IRR under two scenarios. Scenario 1 considers only direct benefits, while Scenario 2 incorporates potential increases in Buleleng Regency’s PAD as indirect benefits. The results show that the project increases travel speed by 21 km/h and saves 1.14 minutes of travel time. Break-even analysis indicates that feasibility can be achieved merely by stimulating a real PAD growth of 3.62%, a highly realistic target compared to the region’s historical growth rate. It is concluded that the investment justification for this project lies in its role as a catalyst for regional economic development, rather than merely in transportation efficiency. This conclusion is robust, as the project’s strategic feasibility remains valid even under pessimistic scenarios. It is recommended that the government integrate regional economic impact analysis into the evaluation of future strategic projects. This study may serve as a framework for measuring indirect benefits in the form of potential PAD increases, which can become an important consideration in evaluating strategic projects that may conventionally appear economically unfeasible.